2016
DOI: 10.1007/s11882-016-0664-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of GST Polymorphisms in Air Pollution Exposure and Respiratory Diseases and Allergies

Abstract: Current studies in epidemiological and controlled human experiments found evidence to suggest that GSTs modify the impact of air pollution exposure on respiratory diseases and allergies. Of the nine articles included in this review, all except one identified at least one significant interaction with at least one of glutathione S-transferase pi 1 (GSTP1), glutathione S-transferase mu 1 (GSTM1), or glutathione S-transferase theta 1 (GSTT1) genes and air pollution exposure. The findings of these studies, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In addition to lower levels of superoxide dismutase and catalase, 89 it has been shown that goblet cells express the high-affinity sodium ascorbate cotransporter, which is involved in vitamin C uptake into cells, and that expression of sodium ascorbate cotransporters is inversely related to lung lining fluid vitamin C levels 91 . There is also considerable evidence that polymorphisms in glutathione -cycling enzymes can result in increased susceptibility to air pollution 92, 93, 94. Glutathione-S-transferase (GST)-pi is predominantly expressed in airway epithelial cells, and expression is decreased in the airways of children with asthma 95 .…”
Section: Dysregulation Of the Epithelial Barrier In Asthmatic Patientsmentioning
confidence: 99%
“…In addition to lower levels of superoxide dismutase and catalase, 89 it has been shown that goblet cells express the high-affinity sodium ascorbate cotransporter, which is involved in vitamin C uptake into cells, and that expression of sodium ascorbate cotransporters is inversely related to lung lining fluid vitamin C levels 91 . There is also considerable evidence that polymorphisms in glutathione -cycling enzymes can result in increased susceptibility to air pollution 92, 93, 94. Glutathione-S-transferase (GST)-pi is predominantly expressed in airway epithelial cells, and expression is decreased in the airways of children with asthma 95 .…”
Section: Dysregulation Of the Epithelial Barrier In Asthmatic Patientsmentioning
confidence: 99%
“…Specifically, genes belonging to the glutathione S-transferase (GST) family are of particular interest because of their role in cellular protection against oxidative stress, which is a potential pathway for toxic air pollution effects. 12 Recently, evidence has found that children with GST pi 1 (GSTP1) and GST Mu 1 (GSTM1) genotypes may constitute a susceptible population at increased risk of asthma associated with TRAP 13,14 and of childhood AD associated with prenatal smoke exposure. 15 In addition, there is growing evidence that air pollutants activate Toll-like receptor (TLR) signaling, resulting in a pro-inflammatory response in the lung, 16 and a previous study in the PIAMA cohort identified a gene by TRAP interaction for TLR2 and TLR4 variants with respect to asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, genes belonging to the glutathione S‐transferase (GST) family are of particular interest because of their role in cellular protection against oxidative stress, which is a potential pathway for toxic air pollution effects . Recently, evidence has found that children with GST pi 1 ( GSTP1) and GST Mu 1 ( GSTM1) genotypes may constitute a susceptible population at increased risk of asthma associated with TRAP and of childhood AD associated with prenatal smoke exposure …”
Section: Introductionmentioning
confidence: 99%
“…Protection against oxidative stress includes conjugation of reactive intermediates with glutathione which is mediated by GSTs. Expression and genetic variants of GSTs affect the capacity of detoxification (Bowatte et al., 2016). Decreased gene expression of GSTM1 and GSTP1 was found in lungs of humans with COPD (Tomaki et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other enzymes such as GSTP1, GSTM1 and SOD3 participate in detoxification of reactive metabolites and have a central role in the defence against oxidative stress in the airways (Sahiner et al., 2011). Several studies in humans indicate that genetic variation and induction of the isoenzymes in the CYP family as well as GSTP1, GSTM1 and SOD3 may play a role in the onset of inflammatory processes that might lead to asthma and bronchitis (Bowatte, Lodge, Perret, Matheson, & Dharmage, 2016; Dahl et al., 2008; Gaurav et al., 2017; Korytina, Yanbaeva, Babenkova, Etkina, & Victorova, 2005; Sahiner et al., 2011).…”
Section: Introductionmentioning
confidence: 99%